Converging Peril : Climate Change and Conflict in the Southern Philippines - Ewing, J. Jackson (2016)
The provinces of the Autonomous Region of Muslim Mindanao (ARMM) in the southern Philippines are experiencing convergence risks from climate change and violent conflict. These provinces combine a natural vulnerability to the effects of climate change with a low adaptive capacity to meet the challenges posed by detrimental climate shifts. Provinces in the ARMM depend heavily upon coastal resources, which are highly susceptible to climatedriven ecological changes, for the livelihoods and life support systems of their populations. These same provinces possess some of the lowest development indicators in the Philippine archipelago, which makes adaptation to the effects of climate change substantially more difficult. Physical and societal vulnerability to climate change in ARMM provinces combines with an established conflict dynamic between elements of the Moro population and the Government of the Republic of the Philippines (GRP). Because of the connectedness of these issues, the potential for climate change to lead to greater deprivation and social challenges in the ARMM is an important consideration for peacebuilding efforts in the region. Recognising the potential relationships between climate change and conflict in Mindanao is an important step towards employing integrated approaches that address both climate and security challenges. While increasingly clear scientific evidence demonstrates that climate change poses significant challenges for many sectors of society, determining the appropriate place for climate change in security studies remains a difficult task. Climate change requires a re-evaluation of traditional security norms that respects its potential to exacerbate conflict dynamics and make peacebuilding efforts more difficult. A comprehensive approach to security that includes conflict drivers from a multitude of sectors represents the most appropriate framework for addressing climate and conflict challenges. This working paper argues that recognising the interplay between climate change and insecurity is a central step towards adopting comprehensive strategies for promoting stability in Mindanao and other vulnerable regions. Integrated strategies that address adaptation to climate change as well as traditional conflict drivers provide a progressive way to address intersecting climate and conflict vulnerability.